Country’s governance quality impact on cloud computing adoption in the EU enterprises - Lejla Karamujic (Investigaciones Regionales - Journal of Regional Research)
Cloud computing is widely recognised as a key technology that enables digitalisation, fuelling the digital economy growth. Using World Bank Governance Indicators, in this paper we examine how country’s quality of governance (or good governance) impacts the use of cloud computing in the enterprises in the EU, hence aﬀects digitalisation of the EU. In an empirical examination of 27 EU countries over a period from 2014 to 2021, it was found that good governance positively aﬀects cloud computing adoption in the EU enterprises. In support of the institutional theory, we show that the improving country’s governance quality is an important step in accelerating cloud computing adoption by the EU enterprises, the ﬁnding providing an important input to the EU government in their execution of the Industrial Strategy 2030, in which digitalisation and cloud computing adoption play an important role. Businesses operating in the EU countries with higher quality of governance are more likely to implement cloud computing in their operations, a cost and performance beneﬁting technology, a valuable insight to the EU enterprises, which gain direct beneﬁts from increased cloud computing adoption in their businesses.